Dependency on common property water resources of nearby community people in Mymensingh and Kishorgang district of Bangladesh (Progressive Agriculture, 2018)
The research was conducted to assess the dependency on common property water resource of nearby community people in two selected areas of greater Mymensingh. A total of 60 farmers were surveyed from Char Nilokkhiya of Mymensingh district and Char Koromshi of Kishoreganj for collecting necessary data and information using random sampling method during December 2016 to March 2017. It was seen that around 73 percent respondents were engaged in fishing in Char Nilokkhiya and 37 percent respondents were engaged in fishing in Char Koromshi. In Char Nilokkhiya the significant variables were amount of land, religion, and alternate sources of income. In Char Koromshi significant variables were educational level of household head, distance of beel from home, power of relatives, and relation with local government. Gini coefficients show that more inequality prevails in Kishoreganj than Mymensingh in terms of income and land holding. This is because some common water resources are underutilized and some are dominated by elite people. Considering the research findings, some crucial policy recommendations have been arisen which are: necessary steps which may be useful for the farmers to achieve social equity should be properly implemented and initiative for supporting true fishers by institutional credit and arranging technical training to enrich the knowledge of the farmers on fish catching.Progressive Agriculture 29 (1): 45-52, 2018